Using in vitro to in vivo extrapolation (IVIVE) to develop toxicity metrics for human health risk assessment of polybrominated diphenyl ethers (PBDE). Issue 1 (2nd January 2017) - Pree, Krystal L.; Bruce, Erica D.
Abstract: Polybrominated diphenyl ethers (PBDE) are flame retardants found in many industrial components, such as furniture foam, consumer electronics, plastics, and textiles and levels have increased in human beings over the past few decades. PBDE (1) produce adverse neurotoxic effects in mice, (2) are lipophilic, and (3) bioaccumulate in fish. Consequently, PBDE biomagnification may occur, which may be transferred to human beings in amounts that may exert adverse health effects. This investigation uses in vitro models to calculate bioassay-based reference doses in order to develop a human health risk assessment based on the consumption of PBDE-contaminated fish, using in vitro to in vivo extrapolation. The toxicity effects of 10 PBDE congeners were examined and compared among those developed using traditional in vivo mouse studies and in vitro models in this investigation employing rat (Clone-9), HEPG2 and zebrafish liver cells to determine the feasibility of using alternative approaches to develop toxicity metrics to evaluate human health risk.